Knowledge Levels of Fırat University Medical Faculty First Year Students About Sex and AIDS Before and After Education - Polat, S. Aytaç; Ozan, A. Tevfik (Fırat University, 2001)
The study was carried out to determine the level of knowledge about sexual relations and AIDS in first grade medical students before and after education study at the University of Fırat, School of Medicine. Data was based on survey forms that were filled by a total of 101 students. The 66.3% of students were male and 33.7% were female. The mean age was 18,1±0,93 years and 58.4% was graduated from high school. The first three contraceptive methods before education were oral contraceptives (77.2%), condom (51.5%) and intrauterine device (24.8%). The most important knowledge source of students were TV, video or computer in 57.4%, newspaper and magazines in 55.4%, and books in 35.6%. 96.0% of students were aware of AIDS transmission. The first three answers about the tracts of transmission was as follows before and after education; sexully transmission (98.0%-100.0%), blood transfusion (94.1%-98.0%) and from mother to the baby (28.7%-89.1%). In a conclusion, students level of knowledge about sexual relations and AIDS was not sufficient, but improved with given education. It is thought that in every step of education these kind of knowledge must be given.

Bu araştırma, Fırat Üniversitesi Tıp Fakültesi 1. sınıf öğrencilerinin cinsellik ve AIDS konularındaki bilgi düzeylerini; eğitim öncesi ve sonrası değerlendirmek amacıyla yapılmış, bir müdahale araştırmasıdır. Araştırma birinci sınıfta kayıtlı olan 101 öğrenci üzerinde, anket yöntemiyle yapılmıştır. Öğrencilerin %66.3'ü erkek, %33.7'si ise kızdır. Yaş ortalamaları 18.1±0.93 olup, %58.4'ü lise, mezunudur. Öğrencilerin eğitimden önce en iyi bildikleri ilk üç doğum kontrol yöntemi; oral kontraseplifler (%77.2), prezervatif (%51.5) ve RİA (%24.8)'dır. Öğrencilerin cinsel konulardaki en önemli bilgi kaynakları; TV, video ya da bilgisayar (%57.4), gazete ya da dergiler (%55.4) ve kitaplar (%35.6)'dır. Öğrencilerin, %96.0'sı AIDS'in bulaşıcı bir hastalık olduğunu belirtmiştir. Bulaşma yolları ile ilgili olarak ise, eğitimden önce ve sonra verdikleri ilk üç cevap sırasıyla; cinsel ilişkiyle (%98.0-%100.0), kan transfuzyonu ile (%94.1-%98.0) ve anneden bebeğine geçiş (%28.7-%89.1) şeklindedir. Elde edilen verilerden; çalışmaya alınan öğrencilerin cinsel konular ve AIDS hakkında yeterli bilgiye sahip olmadıkları ve verilen eğitim ile bilgi düzeylerinin genel olarak arttığı anlaşılmaktadır. Sonuçlar, bu konuların eğitimin her kademesi içerisinde ele alınmasının gerekli olduğunu düşündürmektedir.
FIRAT ÜNİVERSİTESİ TIP FAKÜLTESİ 1. SINIF ÖĞRENCİLERİNİN EĞİTİM ÖNCESİ VE SONRASI CİNSELLİK VE AIDS KONULARINDAKİ BİLGİ DÜZEYLERİ